Pengaruh Beban Kerja, Work Life Balance dan Konflik Kerja Terhadap Stres Kerja (Studi Pada Karyawan di PT Jamkrindo Cabang Kabupaten Tangerang) - Muhammad Aqib Fikri; Widi Wahyudi (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This research aims to improve work stress at PT Jamkrindo with the title research into the influence of Work Load, Work Life Balance, and Work Conflict on work stress in employees of PT Jamkrindo Tangerang Regency branch. The population used in this research were employees of PT Jamkrindo Tangerang Regency branch. The sample in this study was 54 respondents and the technique used was nonprobability sampling technique. The analytical tool used is quantitative analysis, namely multiple linear regression analysis using the SPSS version 22.0 program and Microsoft Excel 2021. The results of this research show that workload (X1), work life balance(X2), and work conflict have a significant effect (X3) on work stress (Y)